Analisis Yuridis Normatif Undang-Undang Perlindungan Tindak Pidana Kekerasan Terhadap Anak - Muhammad Farhan Hasan; Asep Suherman (CV. ITTC INDONESIA, 2024)
Domestic Violence or abbreviated as KDRT is a problem that is often found throughout the world and this is a topic that has never been resolved. Domestic violence is a social phenomenon that has been going on for a long time in some households in the world. This problem is a serious problem that involves violations of Human Rights (HAM). Child violence includes physical, psychological, sexual violence, and neglect. UNICEF defines violence against children as